A rare case of an ovarian ectopic pregnancy - Bendre, Kirti; Kulkarni, Sharvari; Gejele, Sulbha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Ovarian pregnancy is a rare form of the non-tubal ectopic pregnancy accounting for 3% of all ectopic pregnancies (incidence: 1.38-1.5%). Diagnosis is mostly missed and patients usually present with hemoperitoneum and shock since ovaries have rich blood supply. We report a case of a 42-year-old G4P3L3 with 6 weeks of amenorrhea with severe pain in abdomen, giddiness, spotting p/v. Beta hCG was 5380 mIU/ml, hemoglobin (Hb): 4 gm%, with ultrasonography (USG) was s/o left adnexal mass with massive hemoperitoneum. Patient taken for emergency exploratory laparotomy with Intraoperative findings showing massive hemoperitoneum with b/l tubes being normal, left ovary having 1.5 cm cystic mass which was bleeding. Left partial oophorectomy with D and C done. Histopathology report suggestive of normal tubes and ovary with syncytiotrophoblast s/o ruptured ovarian ectopic pregnancy.